IL-6 produced by prostate epithelial cells stimulated with Trichomonas vaginalis promotes proliferation of prostate cancer cells by inducing M2 polarization of THP-1-derived macrophages. - Ik-Hwan Han; Hyun-Ouk Song; Jae-Sook Ryu (Public Library of Science (PLoS), 2020)
Trichomonas vaginalis (Tv), a protozoan parasite causing sexually-transmitted disease, has been detected in tissue of prostatitis, benign prostatic hyperplasia (BPH) and prostate cancer (PCa). IL-6, a mediator of chronic inflammation, induces the progression of prostate cancer, and influences the polarization of M2 macrophages, which are the main tumor-associated macrophages. We investigated whether IL-6 produced by human prostate epithelial cells stimulated with Tv induces the M2 polarization of THP-1-derived macrophages, which in turn promotes the progression of PCa. Conditioned medium was prepared from Tv-infected (TCM) and uninfected (CM) prostate epithelial cells (RWPE-1). Thereafter conditioned medium was prepared from macrophages after incubation with CM (M-CM) or TCM (M-TCM). RWPE-1 cells infected with Tv produced IL-6 and chemokines such as CCL2 and CXCL8. When human macrophages were treated with conditioned medium of RWPE-1 cells co-cultured with Tv (TCM), they became polarized to M2-like macrophages as indicated by the production of IL-10 and TGF-β, and the expression of CD36 and arginase-1, which are M2 macrophage markers. Moreover, proliferation of the M2-like macrophages was also increased by TCM. Blockade of IL-6 signaling with IL-6 receptor antibody and JAK inhibitor (Ruxolitinib) inhibited M2 polarization of THP-1-derived macrophages and proliferation of the macrophages. To assess the effect of crosstalk between macrophages and prostate epithelial cells inflamed by Tv infection on the growth of prostate cancer (PCa) cells, PC3, DU145 and LNCaP cells were treated with conditioned medium from THP-1-derived macrophages stimulated with TCM (M-TCM). Proliferation and migration of the PCa cells were significantly increased by the M-TCM. Our findings suggest that IL-6 produced in response to Tv infection of the prostate has an important effect on the tumor microenvironment by promoting progression of PCa cells following induction of M2 macrophage polarization.